Cloud–cloud collisions and triggered star formation. (3rd December 2020) - Fukui, Yasuo; Habe, Asao; Inoue, Tsuyoshi; Enokiya, Rei; Tachihara, Kengo
Abstract: Star formation is a fundamental process for galactic evolution. One issue over the last several decades has been determining whether star formation is induced by external triggers or self-regulated in a closed system. The role of an external trigger, which can effectively collect mass in a small volume, has attracted particular attention in connection with the formation of massive stellar clusters, which in extreme cases may lead to starbursts. Recent observations have revealed massive cluster formation triggered by cloud–cloud collisions in nearby interacting galaxies, including the Magellanic system and the Antennae Galaxies as well as almost all well-known high-mass star-forming regions in the Milky Way, such as RCW 120, M 20, M 42, NGC 6334, etc. Theoretical efforts are going into the foundation for the mass compression that causes massive cluster/star formation. Here, we review the recent progress on cloud–cloud collisions and the triggered star-cluster formation, and discuss future prospects for this area of study.